Pre-pubertal Growth of PE (Peranakan Ettawa) Goat and it’s Crosses with Boer Buck in Lombok Island, Indonesia - Fitriani, Baiq Mesy Darita; Ashari, Muhammad; Hidjaz, Tahyah; Pribadi, Lalu Wira (Jurnal Biologi Tropis, 2025)
The research which was designed to investigate the pre-pubertal growth performance of PE (Peranakan Ettawa) Goat and Boer >< PE crossbred kids under different birth type, was carried out by observing the weaning weight (BS90), weight at puberty (BB160) and pre-pubertal daily weight gain (PBBHpra-pubertas) of 43 Peranakan Ettawa (PE), 35 Boerawa Grade-1 (B.PE), 39 Boerawa Grade-2 (B2.PE), and 20 Boerawa Grade-3 (B3.PE) kids, each of which consists of single and twins birth type, determined purposively for the population of each genotype on 2 goat farms in Lombok Island. Data were obtained by directly measurement on body weight at weaning and puberty, then the pre-pubertal growth are calculated. The results showed, that the average pre-puberty growth performance of PE goats and their crosses with Boer, based on the daily weight gain (PBBHpre-pubery) achieved, is 0.064±0.019 kg for PE kid goats and 0.089±0.025 kg for Boer >< PE crosses, each depending on the type of birth. The group of kid goats with the highest growth rate is shown by the Single Birth of B.PE group (50% Boer, 50% PE) (KT) with a PBBHpre-pubertal achievement of 0.117±0.032 kg. Grading-up of PE goats through crosses with Boer buck in this study, can increase the average pre-puberty growth performance of their crossbred kids by 29.09%.